An examination of the relation between strategic interaction among industry firms and firm performance - Bayar, Tumennasan; Cornett, Marcia Millon; Erhemjamts, Otgontsetseg; Leverty, Ty; Tehranian, Hassan (Journal of Banking & Finance, 2018)
This paper examines the relation between the degree and type of strategic interaction among industry firms and firm performance. As a measure of firm performance, we use data envelopment analysis (DEA) to estimate the efficiency of a firm relative to the ‘best practice’ firms in its industry. We find that firms in industries with higher levels of strategic interaction are less efficient and the negative relation is more pronounced in industries where firms compete in strategic substitutes. This finding is consistent with the idea that there is significantly more cooperation (tacit collusion) under strategic complements than strategic substitutes. We also find that frontier efficiency methodology outperforms other measures of firm performance in explaining the relation between strategic interaction and firm performance.